Opioid Prescription Among Sinus Surgeons. Issue 4 (July 2018) - Arianpour, Khashayar; Nguyen, Brandon; Yuhan, Brian; Svider, Peter F.; Eloy, Jean Anderson; Folbe, Adam J.
Background: Misuse and diversion of opioids have contributed to the U.S. opioid crisis, making an understanding of specialty-specific and procedure-specific trends essential. Objective: The objective of this analysis was to evaluate nationwide trends in opioid prescribing patterns among sinus surgeons performing functional endoscopic sinus surgery and maxillary sinus balloon dilation, specifically examining factors associated with variations. Methods: High-volume sinus surgeons were identified through the Centers for Medicare and Medicaid Services database and cross-referenced against prescriptions to Medicare Part D beneficiaries during 2013 through 2015. Number of opioid prescriptions, prescription lengths, and demographic information were obtained. Results: This cohort of 570 surgeons wrote 21, 042 opioid prescriptions (5.4 days per prescription) in 2015, with 80.3% and 54.7% writing >10 and >25 prescriptions, respectively. Surgeons writing a greater amount of prescriptions wrote lengthier courses throughout all 3 years ( P  = .01, P  = .002, P  = .003). Female otolaryngologists wrote lengthier prescriptions (6.2 vs 5.3 days, P  = .01). Early career otolaryngologists (≤10 years) offered fewer prescriptions compared to those who had greater experience (31.1 vs 39.3, P  = .02). Moreover, 73.6% of fellowship-trained otolaryngologists offered >10 prescriptions versus 82.7% of nonfellowship-trained otolaryngologists ( P  = .02). Practitioners in the South on average prescribed the greatest amount of opioids ( P  < .05). Conclusion: A majority of sinus surgeons prescribe ≥25 opioid prescriptions annually, with otolaryngologists who write a greater amount of prescriptions writing lengthier courses. As the mean opioid prescription length is 5.4 days, recent legislation limiting opioid prescriptions to 5 days may only have a modest impact for preventing the diversion of perioperative opioid prescriptions. These data suggest further standardized guidelines may be beneficial in elucidating the appropriate indications for the prescription of opioids among sinus surgeons.